(untitled) (Technological Innovations Journal, 2023)
The essay delves into the perspective of management in a digital environment marked by the dynamics and speed characteristic of globalization. The role of the manager is contextualized in the urgent need to stay updated, adopting new tools, and emphasizing the crucial integration of Artificial Intelligence. Through a documentary review, the essay proposes an approach that highlights the importance of the administrative process, giving particular relevance to forecasting as a crucial element before planning. This approach aims to enhance the efficiency, effectiveness, and holistic vision of the manager, enriching their performance through knowledge. The work seeks to reaffirm, from the standpoint of management, the importance of incorporating technological tools, with a special emphasis on Artificial Intelligence. Encouraging reflection, the essay urges further exploration of the presented themes, essential in daily life and fundamental for generating broader and deeper knowledge in the field of business administration in the digital age.